Study on spoilage capability and VBNC state formation and recovery of Lactobacillus plantarum. (September 2017) - Liu, Junyan; Li, Lin; Li, Bing; Peters, Brian M.; Deng, Yang; Xu, Zhenbo; Shirtliff, Mark E.
Abstract: Objective: The present study aimed at investigating the capability of L. plantarum strain BM-LP14723 to enter into and recover from the viable but nonculturable (VBNC) state and to cause beer spoilage. Methods: VBNC state was induced by incubating in beer with subculturing or low temperature treatment. Culturable, total, and viable cells numbers were assessed by MRS agar plate counting, acridine orange direct counting, and Live/Dead BacLight bacterial viability kit, respectively. Organic acids concentrations were measured by reversed-phase high performance liquid chromatography. Results: VBNC L. plantarum cells were detected after 189 ± 1.9 days low temperature treatment or 29 ± 0.7 subcultures in beer. The VBNC L. plantarum retained spoilage capability. Addition of catalase is an effective method for the recovery of the VBNC L. plantarum cells. Conclusion: L. plantarum strain BM-LP14723 is capable of entering into and recovery from the VBNC state and maintained spoilage capability. The current study presented that beer-spoilage L. plantarum can hide both in breweries and during transporting and marketing process and thus lead to beer-spoilage incidents. Highlights: L. plantarum strain BM-LP14723 is capable of entering into the VBNC state in beer. The VBNC L. plantarum cells acquire similar beer-spoilage capability with culturable cells. The addition of catalase is an effective method for the recovery of VBNC L. plantarum cells.